2021
DOI: 10.1126/sciadv.abg9910
|View full text |Cite
|
Sign up to set email alerts
|

Daytime eating prevents internal circadian misalignment and glucose intolerance in night work

Abstract: Night work increases diabetes risk. Misalignment between the central circadian "clock" and daily behaviors, typical in night workers, impairs glucose tolerance, likely due to internal misalignment between central and peripheral circadian rhythms. Whether appropriate circadian alignment of eating can prevent internal circadian misalignment and glucose intolerance is unknown. In a 14-day circadian paradigm, we assessed glycemic control during simulated night work with either nighttime or daytime eating. Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 51 publications
3
45
0
1
Order By: Relevance
“…Alternatively, as we suggested above, the daytime melatonin increase may reflect a less robust output of the central circadian pacemaker, which may result in weakened peripheral tissue entrainment 18,71,72 . In this case, under our night shift conditions in which also the meal schedule was inverted, a different re‐entrainment rate between central and peripheral oscillators may lead to internal desynchrony which has been proposed to compromise glucose control 73,74 . Whatever the underlying mechanism, this finding has potential practical implications.…”
Section: Discussionmentioning
confidence: 65%
“…Alternatively, as we suggested above, the daytime melatonin increase may reflect a less robust output of the central circadian pacemaker, which may result in weakened peripheral tissue entrainment 18,71,72 . In this case, under our night shift conditions in which also the meal schedule was inverted, a different re‐entrainment rate between central and peripheral oscillators may lead to internal desynchrony which has been proposed to compromise glucose control 73,74 . Whatever the underlying mechanism, this finding has potential practical implications.…”
Section: Discussionmentioning
confidence: 65%
“…Research in this area is of particular interest for night workers who typically eat during the night [55]. Recent laboratory research has demonstrated the beneficial effect for glucose metabolism of maintaining a daytime eating window even while working (simulated) night shifts [85][86][87][88]. To extend this research, additional consideration of TRE for those working night shifts is needed; in particular, this would determine the impact In shortening the eating window, TRE reduces the amount of time the body is required to metabolise food and lengthens the daily fast period, arguably allowing for greater metabolic recovery [14,16,22,41,50].…”
Section: Time-restricted Eating Circadian Disruption and Cardiometabo...mentioning
confidence: 99%
“…Recent laboratory research has demonstrated the beneficial effect for glucose metabolism of maintaining a daytime eating window even while working (simulated) night shifts [85][86][87][88].…”
Section: Time-restricted Eating Circadian Disruption and Cardiometabo...mentioning
confidence: 99%
“…This was followed by a series of studies demonstrating that "b-cell rest" or acute inhibition of insulin secretion, could restore b-cell function (first phase insulin secretion), insulin/Ca 2+ pulsatility, and insulin content in obesity and T2DM (144)(145)(146)(147)(148). Chronic bcell stimulation common to high fat feeding/obesity (149) and circadian disruption (21,22) result in both b-cell dysfunction and apoptosis which have been shown to be reversed by ADF (49,150), tRF (47,151,152), and a FMD (153). Specifically, a 12-week ADF regimen protected mice from HF diet induced b-cell dysfunction and failure (49), which was associated with enhanced GSIS, restored islet insulin content, and reduced apoptosis contingent on ADF activation of the autophagy-lysosome pathway.…”
Section: Islet Response To Time-dependent Regulation Of Food Intakementioning
confidence: 99%